Transformational Leadership of KH. Yusuf Hasyim in Preserving Traditional Islamic Education at Pesantren Tebuireng - Yusuf, Mochamad Irfan; Maimun, Agus; Basri; As'ad, Muhammad (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2024)
This study examines the transformational leadership of KH. Muhammad Yusuf Hasyim in preserving traditional Islamic education at Pesantren Tebuireng, Indonesia. Using a qualitative approach with historical methods, data were collected through interviews, observations, and document analysis. The findings reveal that KH. Yusuf Hasyim exhibited strong characteristics of transformational leadership, including idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. His leadership strategies balanced the preservation of tradition with modernization, integrating Islamic and general education while maintaining the pesantren's identity. The impact was significant, improving the quality of education, modernizing infrastructure, strengthening the pesantren's role in society, and expanding a national alumni network. This research contributes to understanding how transformational leadership principles can be effectively applied in traditional Islamic educational institutions facing modern challenges.